Ordered micropillar array gold electrode increases electrochemical signature of early biofilm attachment - Astorga, Solange E.; Hu, Liang Xing; Marsili, Enrico; Huang, Yizhong (Materials & design, 2020)
Extracellular electron transfer (EET) from microorganisms to insoluble metals and electrodes is relevant to energy recovery from wastewater, green production of high-added value chemicals, and biosensors for food, environmental, and clinical applications. Microstructured electrode surfaces increase EET rate in bioelectrochemical systems, thus enabling higher sensibility and power output as well as the detection of bacteria and biofilms in bioelectrochemical sensors. However, many aspects of the EET process, particularly in early biofilm stages, are still poorly understood. We report a microstructured gold electrode maintained at oxidative potential to support the growth of Escherichia coli, measure the electrochemical output, and analyze the EET rate during early biofilm formation. The charge outputs of the modified electrodes are up to 22% higher than the control electrodes, enabling the electrochemical detection of early E. coli biofilms. The electrode microstructures promote biofilm attachment, as confirmed by field emission scanning electron microscope (FESEM) and confocal laser scanning microscope (CLSM) imaging. Following biofilm formation, the resistance to charge transfer at the biofilm-electrode interface decreases and the capacitance increases as shown by EIS analysis. Overall, these results contribute to the understanding of EET in early biofilms, towards developing sensitive bioelectrochemical sensors for biofilm detection. [Display omitted] •Electrochemical signature of E. coli early biofilm was measured on microstructured electrodes.•Microstructured electrodes enhanced early biofilm attachment.•Microstructured electrodes increased EET rate and detection of early biofilms by 22%.•Biofilm formation decreased interfacial resistance via impedance spectroscopy.•Electronic and confocal microscopy confirm that biofilm forms near electrode microstructures.